Targeting Metabolic Pathways of Myeloid Cells Improves Cancer Immunotherapy - Li, Jianying; Bolyard, Chelsea; Xin, Gang; Li, Zihai (Frontiers in Cell and Developmental Biology, 2021)
Tumor-infiltrating myeloid cells are a prominent pro-tumorigenic immune cell population that limit host anti-tumor immunity and present a significant obstacle for many cancer immunotherapies. Targeting the mechanisms regulating myeloid cell function within the tumor microenvironment may overcome immunotherapy resistance in some cancers. Recent discoveries in the emerging field of immunometabolism reveal that the metabolic profiles of intratumoral myeloid cells is rewired to adapt to the nutrition-limited tumor microenvironment, and this shapes their pro-tumor phenotypes. Interestingly, metabolic modulation can shift these myeloid cells toward the immune-stimulating anti-tumor phenotype. In this review, we will highlight the roles of specific metabolic pathways in the activation and function of myeloid cells, and discuss the therapeutic value of metabolically reprogramming myeloid cells to augment and improve outcomes with cancer immunotherapy.